Analisis Peran Produser Sebagai Gatekeeper di Radio OZ Jakarta (Studi Kasus Seleksi Konten Siaran) - Muhammad Abel Aldhan; Anisti; Tuty Mutiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Rapid development in the digital era has brought about a major transformation in the mass media industry, including radio media. Mass media plays an important role as the main source of information for modern society and continues to innovate to remain relevant amidst increasingly tight industry competition. Radio, as one of the oldest electronic media, continues to exist by making various adaptations, both in content and broadcasting technology. In the radio broadcasting process, producers have a strategic role as gatekeepers who are responsible for filtering and determining broadcast content that is worthy of being conveyed to the public. This study aims to analyze the role of producers as gatekeepers in the selection of broadcast content on Radio OZ, a private radio station known for its creative programs and clear audience segmentation. The study uses a case study approach to gain an in-depth understanding of the content selection mechanism, the standards used, and the dynamics of decision-making behind the scenes. The results of this study are expected to contribute to media communication studies, especially in understanding gatekeeping practices in the radio broadcasting industry, and can be a reference for media actors in improving the quality and professionalism of broadcasts.